TINGKAT PERUBAHAN STRUKTUR DAN KOMPOSISI VEGETASI HUTAN AKIBAT PEMANENAN DI PT. BINA MULTI ALAM LESTARI PROVINSI KALIMANTAN TENGAH: The Structure and Composition of Vegetations in the Logged Over Forest with Selective Cutting and Strips Planting Silvicultural System in PT Bina Multi Alam Lestari, Central Kalimantan Province - Chelnavia; Bambang Juniarto; Stefanus Sius Lara (HUTAN TROPIKA, 2021)
The Indonesian Selective Cutting and Planting Silvicultural System (ISCP) has beenapplied to manage natural production forests since 1989. This system was revised in1993 and 2009. This study aims to determine the condition of natural forests afterlogging at PT Bina Multi Alam Lestari, Central Kalimantan Province. The study wasconducted using the plotted plot method proportionally in P-8 Block of RKTUPHHKHA at 2021. The results showed that the structure and composition of the vegetation inthe forest after being harvested using the TPTI silvicultural system at PT Bina MultiAlam Lestari was still well maintained. The meranti tree group dominated the tree levelbefore and after harvesting with INPs of 141 and 135.56, respectively, as well as for thepole level with INPs of 108.56 and 106.33, respectively. Meanwhile, at the seedling andsapling levels, other commercial groups (non dipterocarps) were dominated. Speciesdiversity are high with a range of values of H' 3.1 to 3.3 and species richness rangedfrom moderate to high with a range of values from 3.94 to 6.68. The level of vegetationdensity is still well maintained and is above the standards set by the Ministry ofEnvironment and Forestry. The distribution of vegetation diameter in the forest beforeand after harvesting still resembles the condition of mixed natural forest (unaged standforest) with an inverted J pattern. Natural forest harvesting activities using the TPTIsilvicultural system at PT Bina Multi Alam Lestari in the RKTUPHHK-HA Block in2021 did not cause significant damage and environmental conditions are still wellmaintained.Keywords: Natural forest, Important Value Index, diversity, richness, density